Novel gusset plate design using high strength steel and heat treatment. (June 2019) - Mohammadi, Hossein; Becker, Tracy C.; Zurob, Hatem
Abstract: Gusset plates for high seismic regions are designed to allow brace buckling while minimizing damage to the beam or column by having large rotational capacity. The conventional approach is to use linear fold lines to permit the rotation, which can result in overly large plates. A more compact design uses elliptical fold lines, but both designs can lead to damage to welds with surrounding components. In this paper, a new approach is proposed by defining a yield path through the use of a locally weakened zone created through heat treatment. In this method, inelastic deformation will be concentrated into the weakened zone. The objective of the research is to develop a connection in which the failure mechanism is tightly controlled, which will eliminate unexpected damage mechanisms and result in small gusset plate designs. A series of microhardness, tensile, and bend tests are performed on the heat treated steel samples to study the effect of heat treatment on their mechanical properties. A design methodology for the heat treated gusset plate is proposed, and finite element analysis is used to compare the behavior of the proposed gusset plates. Highlights: Proposes new design methodology for gusset plates in braced frames using local heat treatment. Shows results from heat treatment of common structural materials. Shows numerical results of proposed design method showing shifting of damage away from beam/column connections.